Integration of Ukraine to the global value chains - Vitalii Venger; Nataliia Romanovska; Maryna Chyzhevska (Comparative Economic Research. Central and Eastern Europe, 2022)
The article considers the theoretical and methodological approaches to global value chains when measuring international trade. Global trends in the modern development of international trade are analysed, and the main challenges of international trade policy for Ukraine are characterised. It is established that the modern structure of the Ukrainian economy was formed under the influence of external factors. The authors propose that, over time, the influence of the global economy on the dynamics and structure of the Ukrainian economy will continually intensify. The prospects of Ukraine's integration into global value chains are examined, and the authors found that the structure of Ukrainian exports of goods coincides with the structure of world exports only partially. Ukrainian export of goods is characterised by a low share of highly processed industrial products and a high share of low value-added products, in particular, basic metals and agriculture and food industry products. The export of domestic high-tech goods is constantly decreasing compared to developed countries, and its share in the world export of high-tech goods is insignificant. To ensure the acceleration of GDP growth in Ukraine, it is important not only to increase exports, but also to increase the export of high-tech goods
Keywords: F15; F20; F29; 330; international trade; integration; global value chains; export; import; high-tech goods